Efeitos do precondicionamento isquêmico associado à diferentes soluções de preservação, no intestino delgado preservado hipotermicamente - Neves, José de Souza [UNIFESP] (2011)
BACKGROUND: The preservation of intestinal grafts is a determining factor for the success of small intestine transplantation. OBJECTIVE: To evaluate the effects of ischemic preconditioning associated with Belzer, Celsior, Custodiol and Ringer-Lactate solution in the intestinal preservation and which of these solutions, alone, has better performance. METHODS: We formed randomly, four groups of 14 male Wistar rats weighing between 250 and 300 grams, all of then underwent laparotomy and collection 20cm of ileum for preservation under hypothermia, in Ringer solution (RL), Celsior (Cs), Custodiol (Cust) and Belzer (Belz), for a period of 24 hours. Prior to collection of the ileal segment, half the animals in each group was subjected to ischemic preconditioning of the small intestine (IPC), which consisted of occlusion of superior mesenteric artery for 10 minutes followed by release of the flow (reperfusion) for the same period. During the period of preservation, intestinal samples were collected for four times: with Zero, 12, 18 and 24 hours. In each of these moments were performed: analysis of the degree of mucosal injury (score of Park et al.); dosage of tecidual acid malondialdehyde (MDA) in nmol/mg; quantification of apoptosis in intestinal villi by immunohistochemistry with anti-caspase3. The statistical tests used were ANOVA, Tukey, Kruskal-Wallis and Mann-Whitney; p-values<0.05 were considered significant. RESULTS: In animals without ipc, MDA values, degree of mucosal injury and apoptosis were higher in RL group, and apoptosis was significantly lower in Cs and Belz (p<0.05). In groups with the ipc, RL showed higher MDA values at 18 and 24 hours of preservation (p<0.05). The grades of mucosal injury and apoptosis, except for zero hour, were higher in RL and Cust and lower in the Cs and Belz group, CONCLUSIONS: Celsior and Belzer solutions had better protective effects on intestinal graft, and these effects were augmented by ischemic preconditioning.